STRUKTUR KEPEMILIKAN ASING, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL PENGARUHNYA TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Edison, Acep (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This research is an empirical study on main sector companies listed on the Indonesia Stock Exchange in 2013-2014. The objective of the research is to analyze and to measure the effect of foreign ownership structure, institutional ownership structure, and managerial ownership structure on the disclosure of Corporate Social Responsibility (CSR) activities. Data were collected using purposive sampling technique. Multiple linear regression was used to analyze the data, applying Eviews 8.0. Findings of the study show that the average score of the foreign ownership structure, institutional ownership structure, managerial ownership structure, and CSR disclosure has different changes on each company. Research findings also show that foreign ownership structure, institutional ownership structure, and managerial ownership structure, partially, have significant effects on the disclosure of CSR. Foreign ownership structure, institutional ownership structure, and managerial ownership structure also, simultaneously,have significant effects on CSR disclosure. Keywords: Foreign Ownership Structure, Institutional Ownership Structure, Managerial Ownership Structure, Disclosure of CSR.